The Relationship of Teachers' Personal Competencies and Parents' Permissive Patterns with Adolescent Cyberbullying Behavior - Putro, Hendro Yulius Suryo; Rachman, Ali (Bisma The Journal of Counseling, 2022)
This study was conducted to determine the relationship between teacher personality competencies and permissive parenting patterns with cyberbullying behavior in early adolescents. The subjects of this study were 139 young people at the beginning of junior high school in Mojokerto. The cyberbullying behavior scale consists of 30 authentic items with = 0.958, the teacher's personal competence scale consists of 22 authentic items with = 0.890 and the permissive parenting style scale consists of 26 authentic items with = 0.901. The results showed that the teacher's personality competence and the permissive parenting of parents together had a very significant relationship with the tendency of cyberbullying behavior. The results of the analysis of this study also show that there is a negative relationship between the teacher's personality competence and the tendency of cyberbullying behavior. This means that the higher the teacher's personality competence, the lower the cyberbullying behavior of early adolescents. The correlation between permissive parenting and cyberbullying behavior shows a positive correlation. This means that the more permissive the parenting pattern, the higher the cyberbullying behavior of early adolescents.